Evaluasi Model Kirkpatrick Pelatihan Ms Office Tingkat Lanjutan Di Pusdiklat Sekretariat Jenderal Dan Badan Keahlian Dewan Perwakilan Rakyat - Budi Subandriyo (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2020)
Training is carried out by organizations or agencies to facilitate employees in improving their work-related competencies. The Ms Office Advanced Training aims to provide knowledge and / or mastery of skills related to ASN work, so that participants are able to carry out their duties and responsibilities in a professional manner, as an integral part of the career guidance and work performance system. Such training is regularly held, but whether the training objectives that have been carried out have been achieved optimally. In order to parse the problem, the writer evaluates the kickpatrick model approach. Evaluation is needed to identify the strengths and weaknesses of the program, including knowing whether the learning objectives are appropriate or need improvement. This research involved all 14 participants. The data obtained were analyzed using descriptive analysis and nonparamteric statistical analysis with the Wilcoxon signed ranks test. Based on the analysis of the data it can be concluded, the reaction level shows satisfactory results with an average value of 84.03. Viewed from the level of learning (learning), based on the pretest and posttest scores indicate success, with the existence of positive and significant differences.